2021
DOI: 10.1002/gps.5556
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression, anxiety, and apathy symptoms across dementia stages: A systematic review and meta‐analysis

Abstract: Objective The present study aimed to resolve inconsistency in reported prevalence of affective symptoms by dementia stage. Methods/Design We conducted a meta‐analysis of studies with data on dementia stage and prevalence of depression, anxiety, or apathy assessed using validated tools. We performed random‐effects meta‐analysis and subgroup analysis on symptom prevalence by dementia stage, according to CDR. Results The meta‐analysis included 5897 people with dementia from 20 studies. Prevalence rates of depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 62 publications
5
85
0
Order By: Relevance
“…The small decline in the proportion of PwD who reported mood problems in both the pre-pandemic and pandemic groups is consistent with previous evidence ( 19 , 30 ). This effect was larger in the pandemic group, suggesting that some circumstances related to COVID-19 led to a reduction in the proportion of PwD having mood problems.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The small decline in the proportion of PwD who reported mood problems in both the pre-pandemic and pandemic groups is consistent with previous evidence ( 19 , 30 ). This effect was larger in the pandemic group, suggesting that some circumstances related to COVID-19 led to a reduction in the proportion of PwD having mood problems.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, findings for six outcomes capturing different facets of mental health and wellbeing consistently suggest that, when considering PwD enrolled in the IDEAL cohort as a group, the pandemic was associated with minimal negative change in mental health and wellbeing and with an improvement in mood and optimism. The small decline in the proportion of PwD who reported mood problems in both the pre-pandemic and pandemic groups is consistent with previous evidence (19,30). This effect was larger in the pandemic group, suggesting that some circumstances related to COVID-19 led to a reduction in the proportion of PwD having mood problems.…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, participants in many studies obtained a low score in the apathy and depression scale at baseline, which may also have influenced the effect of the intervention. Since the prevalence of BPSD is also influenced by the severity of cognitive impairment ( Zhang et al, 2012 ; Leung et al, 2021 ), further studies should consider the influence of this severity on apathy and depression while evaluating non-pharmacological approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also reported that 10–20% of older people with dementia living in the community have apathy or depression, both of which are independently associated with cognitive decline ( Vaingankar et al, 2017 ; Van Dalen et al, 2018 ). A recent systematic review and meta-analysis revealed that the prevalence rate of apathy and depression in dementia was 54 and 39%, respectively ( Leung et al, 2021 ). Among the behavioral and psychological symptoms of dementia (BPSD), caregivers do not pay adequate attention to apathy and depression compared to agitation/aggression; thus, apathy or depression in people with dementia is often ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Although cognitive and functional decline are considered hallmarks of dementia, the vast majority of people living with dementia (PWD) also experience at least one neuropsychiatric symptom (NPS) in the course of the disease [ 1 , 2 ] and NPS are especially prevalent in nursing home residents with dementia [ 3 ]. Depression is among the most frequent NPS in dementia with reported prevalence rates ranging from 20 to 60% [ 4 , 5 ]. Depressive symptoms are known to cause distress, decrease quality of life and exacerbate cognitive and functional impairments in PWD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%